THE EFFECT OF LISTEN-READ-DISCUSS STRATEGY ON READING COMPREHENSION ABILITY ON RECOUNT TEXTS BY THE SECOND YEAR STUDENTS OF SMPN 13 PEKANBARU - Selvi Dasria; Eliwarti Eliwarti; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental research aimed to find out whether there was a significant effect of using Listen-Read-Discuss strategy on reading comprehension ability on recount texts by the second year students of SMPN 13 Pekanbaru. The research design is a pre-experimental research with one group pre-test and post-test dessign. The sample was VIII-10 chosen by using cluster sampling technique. The result of the data analysis showed that mean scores of the pre-test was 60.69 and the mean score of the post-test was 70.35. In other words, the mean scores of the post-test is higher than the pre-test. The result also showed that the value of t-obs was higher than t-table (9.869 > 2.023) at significance level of 5%. It can be concluded that the Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. Hence, there is a significant effect of Listen-Read-Discuss strategy on reading comprehension ability on recount texts by the second year students of SMPN 13 Pekanbaru.Keywords: Effect, Listen-Read-Discuss, Reading Comprehension, Recount Texts.